1999
DOI: 10.1136/bmj.319.7210.600
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of unemployment among construction workers: prospective cohort study

Abstract: Objective To study predictors and consequences of unemployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
3
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 17 publications
3
105
3
7
Order By: Relevance
“…Unhealthy lifestyle behaviors as well as physical and psychosocial work demands might also play a role in exit from paid employment (10). However, the evidence concerning these factors is less consistent.…”
Section: Determinants Of Exit From Work Among Older Workers In Europementioning
confidence: 90%
See 1 more Smart Citation
“…Unhealthy lifestyle behaviors as well as physical and psychosocial work demands might also play a role in exit from paid employment (10). However, the evidence concerning these factors is less consistent.…”
Section: Determinants Of Exit From Work Among Older Workers In Europementioning
confidence: 90%
“…Several studies also reported that workers with a poor health are more likely to become unemployed (4,(7)(8)(9)(10)(11) and, to a smaller extent, to retire before the statutory retirement age (4,11,12).…”
mentioning
confidence: 99%
“…Ja¨ntti et al (2000) discover that regional unemployment has not been associated with mortality among Finns. The studies that use panel data are based on restricted samples covering special groups of workers (Lahelma, 1989;Leino-Arjas et al, 1999;Nyman, 2002). This makes it rather difficult to generalize the results obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relationship between unemployment and (ill) health, today, most researchers assume a co-existence of selection as well as causation mechanisms to account for it (Bartley 1988). Numerous studies have demonstrated the existence of selection effects in the association of unemployment and health behaviours (Jusot et al 2008;Leino-Arjas et al 1999;Ryan et al 1996). One explanation for the cross-sectional association could indeed consist in smokers being more likely to become unemployed than non-smokers.…”
Section: Discussionmentioning
confidence: 99%